Model Yesus Sebagai Guru Agung Menjadi Acuan Bagi Guru Pak Sebagai Pendidik Profesional - Emanuel Kristinus Ndruru; Yuliusman Laia (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The teaching profession is generally recognized as a very respectable, noble and noble profession because the purpose of education is to develop a virtuous and competent human personality. PAK teacher professional development takes place with reference to the description of the profession and life of Jesus as an archetype. There is no more perfect model because the Lord Jesus is the Great Teacher and the truth. The example of the Lord Jesus as the Great Teacher is the main reference for the development of the PAK teacher profession. One effective way to explore and improve these skills is through self-assessment. The PAK teacher evaluation form refers to the description of Jesus as the Great Teacher. Thus, teachers must be able to guide students so that they are ready to face real life and can even become role models. In writing, the writer used a qualitative approach and was chosen as the method used in this study. The purpose of this article is for PAK teachers, which refers to professional educators whose main task is to educate, teach, guide, train, and evaluate student learning outcomes.